Vaccins imparfaits : Un problème épineux dans le développement accéléré des vaccins - Graham, Janice; Peeters Grietens, Koen (Anthropologica, 2024)
While no vaccine can provide 100 percent protection, a high standard of regulatory safety, efficacy and quality is essential for public trust and the uptake of vaccines as essential global public health tools. This article addresses a growing concern that suboptimal “leaky” vaccines threaten emergency response to pandemics as well as routine public health programs. Agile regulatory standards now advance earlier approval of vaccines and therapeutics that may have suboptimal effectiveness. The benefit-harm tradeoffs that play an enormous role in regulatory assessment and all stages of vaccine development and delivery deserve better public scrutiny, transparency, and accountability. Drawing on the case of the first licensed malaria vaccine, RTS,S Mosquirix™, in light of the rapid approval of COVID-19 vaccines, we consider the socio- technical implications of leaky vaccines in global vaccine logics and suggest possibilities for building legitimacy to inform the next generation of regulatory technology policy.